2004
DOI: 10.1111/j.1439-0396.2004.00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glycine and vitamin supplementation on sulphur amino acid utilization by growing cattle

Abstract: Effects of glycine (Gly) and B-vitamins on sulphur amino acid (AA) utilization were studied in growing steers maintained under conditions where methionine (Met) was first limiting. Conditions were generated by limit feeding a diet low in ruminally non-degraded protein and abomasally infusing an AA mixture limiting in Met. Retained N tended (p = 0.07) to improve when steers received 10 mg folate, 10 mg vitamin B6, and 0.10 mg vitamin B12 daily. Hepatic vitamin B12 (p = 0.08) and folate (p = 0.05) concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
1
8
1
Order By: Relevance
“…The pH of the infusate was 5.5. PyridoxineؒHCl (10 mg/d), folic acid (10 mg/d), and cyanocobalamin (100 g/d) were added to the mixture because Lambert et al (2004) demonstrated that steers maintained under our experimental conditions were deficient in one or more of these vitamins. Leucine was dissolved separately and added to the mixture according to treatment (0, 4, or 8 g/d).…”
Section: Methodsmentioning
confidence: 99%
“…The pH of the infusate was 5.5. PyridoxineؒHCl (10 mg/d), folic acid (10 mg/d), and cyanocobalamin (100 g/d) were added to the mixture because Lambert et al (2004) demonstrated that steers maintained under our experimental conditions were deficient in one or more of these vitamins. Leucine was dissolved separately and added to the mixture according to treatment (0, 4, or 8 g/d).…”
Section: Methodsmentioning
confidence: 99%
“…After all AA were dissolved, the 2 solutions of AA were mixed together, dextrose was added (330 g supplying 300 g glucose) to provide an additional energy source, and water was added to bring the total weight of the daily infusate to 4 kg. All steers received 10 mg of pyridoxine·HCl/d, 10 mg of folic acid/d, and 100 μg of cyanocobalamin/d in the abomasal infusate because the experimental diet was deficient in at least one of those vitamins (Lambert et al, 2004). To ensure adequate ruminal ammonia concentrations to support microbial growth, all steers received a ruminal infusion of 10 g of urea/d; this was considered part of the dietary N intake.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…The 3 solutions (AA/dextrose mixture, Glu, and Lys) were mixed together in individual bottles and water was added to bring the daily abomasal infusate weight to 4 kg. Pyridoxine HCl (10 mg/d), folic acid (10 mg/d), and cyanocobalamin (0.1 mg/d) were dissolved and added to the abomasal infusate because steers under these experimental conditions may become deficient in at least one of those vitamins (Lambert et al, 2004).…”
Section: Animals and Treatmentsmentioning
confidence: 99%